Rekonstruksi Makna Semboyan Ki Hajar Dewantara dalam Praktik Pendidikan Islam - Alaika M Bagus Kurnia PS; Imam Fawaid; Dewi Zulaicho; Ilmi Zahrotin Faidzullah Al Hamidy (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
The dichotomy of Islamic education in general seems to be a significant difference and does not find common ground. So the purpose of this research is to bring together the education built globally by Ki Hadjar Dewantara with the integration of educational practices in Indonesia. The method of this research is to use hermeneutic research, that is to interpret the meaning of the motto initiated by Ki Hadjar Dewantara, namely Ing Ngarso Sung Tulodo, Ing Madyo Mangun karso, Tut Wuri Handayani. While the results of this study are, the practice of implementing Islamic education in terms of the object of the actor such as teachers, students and other elements (ie alumni, boarding school administrators or senior students) is the direction and form of interpretation of the motto he initiated. The idea – which is also the slogan of the Ministry of Education – is an infrastructure that cannot be separated and is an educational building that is mutually sustainable. So that the construction of learning patterns, mindsets and habitual patterns of students or students needs to be inspired and applied in such a way as to continue to show a typical Indonesian education that prioritizes adab and knowledge.